Problem Solving Ability and Problem Based Learning - Derry Nugraha; Heri Ginanjar; Rosalina Rolina ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The research was caused by the poor of mathematical problem solving ability of students. This research aimed to compare of mathematical problem solving between students who learned through problem based learning and scientific approach. The method was an experimental method with a pretest-posttest control group design involving two groups and random sampling. At the first and end of learning, the two classes are given a test. The population in this research were Madrasah Aliyah students in Cimahi, while the sample consisted of two randomly selected classes. One class  which was given problem based learning and other class was given a scientific approach. The instrument was a set of  5-item mathematical problem solving test description, then those were analyzed with descriptive and inferential statistics using the help of minitab 17 software. Based on the results of the research, the conclusion was  the improvement of  mathematical problem solving  of students using problem based learning was better than students who use a scientific approach.